The recent trend of e-waste recycling and rare metal recovery in Japan - Itoh, H (WIT Transactions on Ecology and the Environment, 2014)
The efficient resource circulation of rare metals is one of the most important economic and political issues in an industrialized society. Rare and noble metals in e-wastes should be collected separately, treated by advanced processes, and then supplied as raw materials for high technology material production. In Japan, the home appliance recycling law was established in 2001 for recovery of base metals (Fe, Al, Cu, etc.), plastics and flons, subject to large electrical appliances such as TV's, air conditioners, washing machines and refrigerators. Typical waste categories are classified as (1) effluents from plating plants or wastewater treatment industries, (2) e-wastes from electronic substrates, household appliances, and many kinds of batteries, (3) automobiles, tools and structural materials and (4) wastes from incinerators, melting furnaces and power stations. The present paper introduces the recent progress of rare metal recycling in Japan in the context of RMRC.